2019
DOI: 10.1108/meq-08-2019-0176
|View full text |Cite
|
Sign up to set email alerts
|

It is not an investment if it is destroying the planet

Abstract: Purpose The purpose of this paper is to critically examine the existing literature on sustainable investments and propose an integrated conceptual framework for measuring socially responsible investment intention of investors. Design/methodology/approach Based on the theory of planned behaviour, the study discusses an integrated conceptual framework by thoroughly analysing the empirical studies of last 18 years, from 2001 to 2018. Some of the important measures of these studies have been reviewed, such as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Ali et al (2017) also found out that religiosity enhances the intention of Socially Responsible Investment. Given the background of above stated findings, we believe that an investor's religiosity beliefs play a significant role in building or enhancing his/her intention to invest in SRI (Mehta et al, 2019;Singh et al, 2020). Hence, it can be expected that a religious person, despite having insufficient SRI knowledge, might have a positive attitude toward SRI on account of his/her religious beliefs.…”
Section: Moderating Effect Of Religiositymentioning
confidence: 75%
See 1 more Smart Citation
“…Ali et al (2017) also found out that religiosity enhances the intention of Socially Responsible Investment. Given the background of above stated findings, we believe that an investor's religiosity beliefs play a significant role in building or enhancing his/her intention to invest in SRI (Mehta et al, 2019;Singh et al, 2020). Hence, it can be expected that a religious person, despite having insufficient SRI knowledge, might have a positive attitude toward SRI on account of his/her religious beliefs.…”
Section: Moderating Effect Of Religiositymentioning
confidence: 75%
“…Li et al (2019) confirm this by concluding that religious entrepreneurs are keener to invest in socially responsible funds than those who acclaimed themselves to be non-religious. Mehta et al (2019) and Singh et al (2020) have also concluded a moderating effect of religiosity beliefs of investors on the relation between attitude and intention of investing in SRI. Hence, religiosity and faith are instrumental for the willingness toward SRI.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, Paill e et al (2019) show that employees' green behaviors in their workplace are significantly influenced by their personal beliefs. If employees are ethical individuals, they will keep a safe distance from organizations involved in environmentally hazardous activities (Mehta et al, 2019). Based on the above discussion, it is expected that personal beliefs and behaviors of SC managers spill over to their workplace.…”
Section: Domestic Green Behavior and Peb Intentionsmentioning
confidence: 99%
“…The emergence of green debt products has been observed in global financial markets, particularly in financing renewable energy projects (Narayan et al, 2022; Charfeddine & Kahia, 2019) [20,5] . Having a strong green financial system helps in directing social capital towards investments in green proposals and accelerating the modulation to a green economy within the industry (Chen et [6,17,28] . Many businesses are now placing strong emphasis on sustainability and implementation of environment friendly practices that promote a greener and more sustainable future (Desalegn & Tangl, 2022) [10] .…”
Section: Review Of Literaturementioning
confidence: 99%